Separation and identification of bioactive peptides from stem of Tinospora cordifolia (Willd.) Miers - Pachaiappan, R.; Tamboli, E.; Acharya, A.; Su, C.H.; Gopinath, S.C.B.; Chen, Y.; Velusamy, P. (Public Library of Science, 2018)
Enzyme hydrolysates (trypsin, papain, pepsin, a-chymotrypsin, and pepsin-pancreatin) of Tinospora cordifolia stem proteins were analyzed for antioxidant efficacy by measuring (1) 1,1-diphenyl-2-picrylhydrazyl (DPPH center dot) radical scavenging activity, (2) 2,20-azinobis(3-ethyl-benzothiazoline- 6-sulfonic acid) (ABTS(+)) radical scavenging capacity, and (3) Fe2+ chelation. Trypsin hydrolysate showed the strongest DPPH center dot scavenging, while alpha-chymotrypsin hydrolysate exhibited the highest ABTS(+) scavenging and Fe2+ chelation. Undigested protein strongly inhibited the gastrointestinal enzymes, trypsin (50% inhibition at enzyme/substrate ratio = 1: 6.9) and a-chymotrypsin (50% inhibition at enzyme/substrate ratio = 1: 1.82), indicating the prolonged antioxidant effect after ingestion. Furthermore, gel filtration purified peptide fractions of papain hydrolysates exhibited a significantly higher ABTS(+) and superoxide radical scavenging as compared to non-purified digests. Active fraction 9 showing the highest radical scavenging ability was further purified and confirmed by MALDI-TOF MS followed by MS/MS with probable dominant peptide sequences identified are VLYSTPVKM-WEPGR, VITVVATAGSETMR, and HIGININSR. The obtained results revealed that free radical scavenging capacity of papain hydrolysates might be related to its consistently low molecular weight hydrophobic peptides.